Museums & galleries displaying Korea's past and future - Jackson, Ben; Park, Hye-young; Seungeun, Euna Yoo; Eun-ji, Shin (Korea essentials, 2011)
Overview of selected major national and public museums in Seoul, South Korea, as well as the specialized museums and regional national museums.